Introduction to the special issue: Allyship, advocacy, and social justice to support equality for marginalized groups in the workplace - Kossek, Ellen Ernst; Ladge, Jamie; Little, Laura M.; Loyd, Denise Lewin; Smith, Alexis Nicole; Tinsley, Catherine H. (Organizational behavior and human decision processes, 2024)
Allyship is an important topic of growing interest in research and practice for management and organizations. However, research is still in its infancy, often fragmented across disciplines, and lacking conceptual clarity. The purpose of this special issue, “Allyship, Advocacy, and Social Justice to Support Equality for Marginalized Groups in the Workplace” is to enhance understanding of allies and allyship. We argue that allyship is a mechanism for centering social justice, reducing discrimination and inequality, and improving intergroup dynamics, inclusion, social cohesion, well-being, and organizational effectiveness. We note the importance of distinguishing between conceptualization of who is an ally and the different types of allyship in a brief review of the foundational grounding of the research stream. Next, we examine findings and insights from the eight papers in the special issue, examining how they move the field forward. These articles provide a springboard for understanding how to define, measure, and evaluate allyship, and for identifying key dynamics (e.g., marginalization, dominance, identity motivations), antecedents, consequences, contexts, and boundary conditions. We conclude by identifying future research opportunities that leverage this special issue’s content and gaps to address. We believe that improving understanding of how to be an ally, what they do, and the conditions under which allyship is effective, is valuable for enhancing social relationships between and within marginalized and dominant groups in organizations and society.